Pengaruh Gaya Kepemimpinan, Kedisiplinan dan Kepuasan Terhadap Kinerja Karyawan: Studi Kasus PT. YKC Perabot Medan - Sella Namira Nasution; Yahya Tanjung (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This study aims to determine the effect of leadership style, discipline and satisfaction on employee performance (case study of PT. YKC Perabot Medan). The data analysis technique used in this study is using research instrument tests, descriptive statistical tests, and classical assumption tests. hypothesis test and test the coefficient of determination. Data collection techniques used in this research use secondary data and primary data. This research is a comparative research. Information regarding this study was obtained from data collection techniques that had been carried out on research subjects, namely employees of PT. YKC Furniture Medan, a research sample of 115 respondents or a questionnaire given to employees of PT. YKC Furniture Medan. The results of the research show that leadership style (X1) has no effect on employee performance, while the discipline variable (X2) has no effect on employee performance (Y), while satisfaction (X3) has an effect on employee performance (Y).